Fenomena Kecerdasan Emosional dan Pengalaman Kepala Cabang dalam Mengatasi Konflik Internal Karyawan Golden Journey Mojokerto: The Phenomenon of Emotional Intelligence and Branch Manager Experience in Resolving Internal Conflicts Among Employees at Golden Journey Mojokerto - Afifatus Sholikhah; Risa Yulia Agustin (Universitas Nahdlatul Ulama Sidoarjo, 2026)
The aim of this study is to understand the emotional intelligence in leadership style and to examine the experiences of branch managers in managing internal conflicts among employees at the Golden Journey branch in Mojokerto. This method used is qualitative and based on in depth interviews and direct observations as data collection. Data analysis involved copying and presenting the data and drawing conclusions. The informant in this study was a branch manager who had experience in dealing with conflict between employees. The results show that emotional intelligence plays an important role in the resolution of internal conflict by the branch manager of Golden Journey Mojokerto. The branch manager was able to use his emotional intelligence to recognise and control his own emotions, motivate his employees and build relationship with them, thereby creating a pleasant working armosphere.